Formulation and Evaluation of Trolamine Salicylate Microemulsion - Sharma, Prachi (Asian Journal of Pharmaceutics (AJP), 2022)
Aim: The aim of this study was to formulate and perform optimization, characterization, and in-vitro evaluation of microemulsion containing trolamine salicylate (TMS) an anti-inflammatory agent for topical application. Materials and Methods: Microemulsion formulations of TMS were prepared from optimized microemulsion and effects of formulation variables such as solubility in different oils, surfactants and co-surfactants were assessed. Oleic acid was selected as oil phase, tween-80, and ethanol as surfactant and cosurfactant, respectively. From the ternary phase diagrams of surfactant (Tween 80)/cosurfactant (Ethanol) 1:1 ratio and oil (oleic acid), TMS-loaded microemulsion formulation A6* was selected on the basis of clarity. Results and Discussion: The microemulsion formulation A6* was found to be optically clear, transparent, and elegant in appearance, when compared to the other microemulsion formulations with pH values of 5.3–6.5 were showing suitability for topical preparations. The transmission electronic microscopy image of A6* showed that globules were spherical in shape, smooth surface, and indicated the existence of an isotropic dispersion of spherical droplets, leading to the assumption of inverse micelles because of the proportion of the constituents. Particle size of 297 nm indicates that there is a chance that the number of vesicles can interact with a fixed area of stratum corneum, thereby increasing the efficiency in percutaneous uptake. During Ex-vivo permeability study, the flux values and permeability coefficient of TMS Microemulsion (A-6*) were found to be 6.518 μg/cm2 h and 3.259 cm.h-1. The highest cumulative drug release for formulation A*6 was 95.048 ± 0.032% in 8 h. Conclusion: Microemulsion has low interfacial tension and allows excellent contact with skin surface, with the vehicle filling even wrinkles and microscopic gaps. This enhances the vehicle skin drug transfer. They have been used to improve the bioavailability of various poorly soluble drugs including non-steroidal anti-inflammatory drugs. The formulation was in nano range and hence the penetrability of the drug can be increased. Since this type of formulations can be easily developed and prepared; therefore, they can be of great help for the drugs that have less permeation across the skin. Among the distinctive formulations, A6* showed promising results, with respect to drug entrapment and percentage drug release.